Analisis Problematika : Implementasi Program Kurikulum Merdeka di SMA Negeri 1 Taman - Calista Na’ilah Nur Maulidiyah; M.Oky Ramadan; Atta Yusli Salsabil; Rahma Rizkya Ananda Sugiharto; Ayu Wulandari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Facilities and infrastructure are two important main resources used to support student learning processes in schools. The independent curriculum is a curriculum that is taught in class in various flexible ways, so that students are given the opportunity to practice their knowledge of these subjects through various learning methods. The aim of this research is to understand the urgency and strengths and weaknesses of existing infrastructure. is in the implementation of the independent curriculum at SMA Negeri 1 Taman. This observational research is included in the type of descriptive research using a qualitative approach. The instrument used was a questionnaire via Google Form which was given to class X students at SMA Negeri 1 Taman. The results of research conducted through observation show a lack of support for facilities and infrastructure from the school and teaching staff in implementing the independent curriculum program, such as inadequate facilities and less relevant access to learning resources in the school environment, thus creating a significant obstacle to achieving the goals. from the independent curriculum. Therefore, the government needs to work together with schools to consider having an independent curriculum in order to address supply issues both in terms of facilities and infrastructure as well as teacher preparation and to ensure resources are evenly distributed across educational institutions to achieve the goals of the independent curriculum itself by implementing This is their policy towards the independent curriculum running optimally.